TERMINASI HUBUNGAN KONSELING - Riem Malini (Hikmah, 2017)
Termination is one of the stages in counseling where counselor should end counseling, this decision can be done unilaterally or together. It’is a sign that something has been done. As for the stages in termination is to start a new experience, previous experience must be solved and solved, maintain the changes that have been achieved and develop expertise to solve problems that have been obtained from counseling, and act as a reminder that the client is an adult. In termination has several issues, namely termination of individual sessions that serve as a time to determine the next service schedule, and counseling relationships that serve as an important point need to be considered when deciding whether to terminate counseling or not. In addition to the termination issues, there are also some types of counseling terminations that need to be noticed by a counselor that is premature termination, termination of initiative, and termination counselor with a positive note. Keywors:s Termination, Relationships, Counseling